Selection, screening and testing of recombinant Fabs against mutated amyloidogenic gelsolin peptide : the causative agent of hereditary gelsolin amyloidosis - Haavisto, Oskar (My University, 2021)
Extracellular gelsolin is an actin modulating plasma protein that is abnormally digested, due to an amino acid substitution, into amyloidogenic 8 kDa peptides (AGel), the causative agents of hereditary gelsolin amyloidosis. Therapeutics, hitherto, have been inefficient in reversing protein aggregation leading to amyloid diseases in vivo, although, therapeutic antibodies show potential as inhibitors. In this thesis antibody binders were developed against various epitopes of AGel. Previously enriched scFv libraries were converted into Fabs and diversified by shuffling the variable domain genes between the clones, followed by enrichment in three rounds of phage display in various conditions against peptides representing terminal fragments as well as the mutation site, and screening for high-affinity binders by immunoassays and sequencing. Most of the selected binders had an equilibrium dissociation constant around 100 nM, although one N-terminal binder had affinity below 30 nM and the mutation site binder above 225 nM. The inhibition ability of five selected Fabs to prevent the formation of fibrils – in one-to-one stoichiometry and conditions corresponding to extracellular matrix in relation to pH and ionic strength – was revealed in vitro in a thioflavin-T aggregation assay and subsequent transmission electron microscope imaging. Fabs against all AGel fragments prevented aggregation entirely, and the post-assay TEM images revealed a relative reduction in quantity and size of the fibrils. The outcome of this project provides a proof-of-concept and can serve as a natural transition into pre-clinical animal trials. Additionally, conversion into IgG and further affinity maturation is desired to improve affinity and kinetic performance.
Keywords: hereditary gelsolin amyloidosis, antibody, phage display, thioflavin-T aggregation assay